Recent developments in genetics and medically assisted reproduction: from research to clinical applications. (January 2018) - Harper, J.; Aittomäki, K.; Borry, P.; Cornel, M.; de Wert, G.; Dondorp, W.; Geraedts, J.; Gianaroli, L.; Ketterson, K.; Liebaers, I.; Lundin, K.; Mertes, H.; et al.
Abstract Two leading European professional societies, the European Society of Human Genetics and the European Society for Human Reproduction and Embryology, have worked together since 2004 to evaluate the impact of fast research advances at the interface of assisted reproduction and genetics, including their application into clinical practice. In September 2016, the expert panel met for the third time. The topics discussed highlighted important issues covering the impacts of expanded carrier screening, direct-to-consumer genetic testing, voiding of the presumed anonymity of gamete donors by advanced genetic testing, advances in the research of genetic causes underlying male and female infertility, utilisation of massively parallel sequencing in preimplantation genetic testing and non-invasive prenatal screening, mitochondrial replacement in human oocytes, and additionally, issues related to cross-generational epigenetic inheritance following IVF and germline genome editing. The resulting paper represents a consensus of both professional societies involved.